The Little Worlds We Hold: Shaping artistic identity through co-facilitating a community engagement project - Moore, Vija Anna; Tambet, Kärt (Taideyliopiston Sibelius-Akatemia, 2025)
This study, written by Vija Moore and Kärt Tambet, has been conducted to gain greater understanding of how we as musicians are affected by working in community based contexts with music. In this study we deconstruct a project that consisted of two different parts. The first part took place at Sofianlehto Activity Centre, which is a care facility dedicated to providing day activities with a multisensory focus that are specially catered to Helsinki residents with multiple disabilities. There we facilitated weekly music sessions with a group of six participants, during which we tried out different approaches of using music as a tool for expression, communication and participation. The second part of the project was the creation of an artistic outcome of the concert “The Little Worlds We Hold” which was a reflection on the experiences and encounters we had at the Sofianlehto Activity Center. The concert was performed for the general public on the 12th of May 2025 as part of the Global Spring festival at the Helsinki Music Centre. The overarching aim of this study is to investigate how co-facilitating a community engagement project can shape a musical outcome and influence musicians’ artistic identities. To uncover our findings, we approach the research through the main theoretical overarching topic of artistic identity followed by the key concepts of musical identity; community music and community musicianship; participatory and presentational music making; and relationships between health and music. The key concepts are further explored through research methods of duoethnography (Sawyer & Norris, 2016) and arts-based research (Leavy, 2022) that is grounded in a reflexive approach (Bolton, Delderfield, 2018; May & Perry, 2017). The key findings of this research uncover the impact of social interaction in artistic expression, acknowledging the bridging of roles as facilitators and performers, and defining the qualities of artistic expression that are synthesised through emotional experiences. These findings are the outcome of what we experienced in the community engagement project and what became important in composing the music.
Keywords: artistic expression; arts-based research; co-facilitation; community engagement project; duoethnography; musicking; participatory music; presentational music; Toimintakeskus Sofianlehto; Sofianlehto Activity Centre; artistic identity; Global Music